Variable impact of COVID-19 on urgent intervention in Ontario. Issue 8 (26th April 2021) - de Mestral, C; Gomez, D; Sue-Chue-Lam, C; Dossa, F; Nantais, J; Simpson, A N; Urbach, D; Austin, P C; Wilton, A S; Baxter, N N
Abstract : COVID-19 had a variable impact on urgent interventions among hospitalized patients in Ontario Canada.